ACM SIGGRAPH 2011 Papers 2011
DOI: 10.1145/1964921.1964932
|View full text |Cite
|
Sign up to set email alerts
|

Efficient elasticity for character skinning with contact and collisions

Abstract: Figure 1: Our method takes a geometric internal skeleton (left) and a source surface mesh (not pictured) as input. Based on a hexahedral lattice (center) it then simulates a deformed surface (right) obeying self-collision and volumetric elasticity. The example shown here has 106,567 cells and simulates at 5.5 seconds per frame. AbstractWe present a new algorithm for near-interactive simulation of skeleton driven, high resolution elasticity models. Our methodology is used for soft tissue deformation in characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
147
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(147 citation statements)
references
References 38 publications
0
147
0
Order By: Relevance
“…In our current work, we have found that it can be applied to the material model of interest [McAdams et al 2011], and more importantly, to self-collisions.…”
Section: Simulation Preliminariesmentioning
confidence: 99%
See 4 more Smart Citations
“…In our current work, we have found that it can be applied to the material model of interest [McAdams et al 2011], and more importantly, to self-collisions.…”
Section: Simulation Preliminariesmentioning
confidence: 99%
“…In addition to their use in feature animation [Clutterbuck and Jacobs 2010], realistic virtual humans also have numerous medical applications [Hirota et al 2001]. Thus, many efficient methods have been developed, including co-rotational elasticity and multigrid solvers [Zhu et al 2010;McAdams et al 2011;Liu et al 2013]. These full-rank methods are complementary to our current approach.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations